Describing Caregiver and Clinician Experiences with Pediatric Telerehabilitation Across Clinical Disciplines - Meaghan Reitzel; Lori Letts; Cynthia Lennon; Jennifer Lasenby-Lessard; Monika Novak-Pavlic; Briano Di Rezze; Michelle Phoenix (International Journal of Telerehabilitation)
Scope: This study describes the high and low points of caregiver and clinician experiences with pediatric telerehabilitation with consideration for the sustainable adoption of pediatric telerehabilitation beyond the COVID-19 pandemic context.